The Coming-Out of Malaria Gametocytes. (22nd November 2009) - Kuehn, Andrea; Pradel, Gabriele
Abstract : The tropical disease malaria, which results in more than one million deaths annually, is caused by protozoan parasites of the genus Plasmodium and transmitted by blood-feeding Anopheline mosquitoes. Parasite transition from the human host to the mosquito vector is mediated by gametocytes, sexual stages that are formed in human erythrocytes, which therefore play a crucial part in the spread of the tropical disease. The uptake by the blood-feeding mosquito triggers important molecular and cellular changes in the gametocytes, thus mediating the rapid adjustment of the parasite from the warm-blooded host to the insect host and subsequently initiating reproduction. The contact with midgut factors triggers gametocyte activation and results in their egress from the enveloping erythrocyte, which then leads to gamete formation and fertilization. This review summarizes recent findings on the role of gametocytes during transmission to the mosquito and particularly focuses on the molecular mechanisms underlying gametocyte activation and emergence from the host erythrocyte during gametogenesis.